Pengaruh opinion shopping, reputasi auditor, disclosure, dan ukuran perusahaan terhadap penerimaan opini audit going concern pada perusahaan manufaktur 2011-2013 yang listing di bursa efek indonesia - Putri, Tria Widiastuti; Diyanto, Volta; ', Rasuli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The users of financial statements need informations as a basic of their economic decision making. Not only in judging the fairness of financial report or detecting a fraud, but also auditors have responsibility to judge the company ability to maintain company going concern. Going concern audit opinion defined as opinion state by the auditors based on their audit, concludes that substantial doubt exists with regard to the company’s ability to continue functioning as a business entity.In this study, we attempt empirically to investigate the relationship between Opinion Shopping, Auditor Reputation, Disclosure, and Company Size, on receiving a going concern audit opinion of a company. The samples are selected by purposive sampling method. All manufacturing company listed in Indonesia stock Exchange that received going concern audit opinion from 2011-2013 are used as the population. Logistic Regression is used to test the hypothesis.From the results, indicate that Opinion Shopping, Disclosure and Company Size is significantly affect on receiving of going concern audit opinion. While the others Auditor Reputation are not significantly affect on receiving of going concern audit opinion of a company.Keywords: Opinion Shopping, Auditor Reputation, Disclosure, and Company Size.